Catch-up growth and overweight adults in the offspring of young gecko mothers resembling low birth weight infants - Starostová, Zuzana; Píchová, Veronika; Bauerová, Anna; Kubička, Lukáš; Kratochvíl, Lukáš (Biology letters, 2024)
Endothermic and ectothermic amniotes differ in the timing of reproductive onset, with reptiles initiating reproduction before reaching final body size. Long-term consequences of maternal effect for early reptile offspring are poorly explored. We conducted growth experiments to compare the growth of offspring produced by young and older females of gecko Paroedura picta. Young, not fully grown females lay smaller eggs leading to production of smaller offspring. These offspring undergo accelerated growth and ultimately reach a comparable sex-specific final body length as do offspring of older females. Final body length is thus canalized with respect to the maternal effect on egg size. Notably, the offspring of young mothers have a tendency towards larger body mass. Ontogeny of the offspring of young females shares similarities with that of mammalian offspring with low birth weight or early malnutrition, exhibiting catch-up growth and a predisposition to obesity. We highlight the important consequences of early reproduction for offspring in animals that initiate reproduction prior to reaching final body size. Both life-history models and conservation practices should take into account that female lizards might produce the most fit offspring only between reaching their final body length and the onset of reproductive senescence.
Keywords: Male; Overweight; obesity; maternal effect; Mammals; porodní hmotnost; Infant; Reproduction; Mothers; Adult; dospělí; mužské pohlaví; nadváha; rozmnožování; Lizards; catch-up growth; novorozenec; ještěři; savci; reproduction; reptiles; Animals; lidé; ženské pohlaví; Humans; Birth Weight; zvířata; Infant, Newborn; body size; kojenec; Infant, Low Birth Weight; Female; matky; novorozenec s nízkou porodní hmotností